Exercise Interventions in Huntington's Disease: An Individual Patient Data Meta‐Analysis. Issue 7 (18th July 2019) - Playle, Rebecca; Dimitropoulou, Polyxeni; Kelson, Mark; Quinn, Lori; Busse, Monica
ABSTRACT: Background: Physical activity may be beneficial in Huntington's disease (HD); however, studies to date have been underpowered to detect change. We combined data from five randomized controlled feasibility trials using individual patient data meta‐analyses. Methods/Design: All trial interventions comprised a combination of supervised and self‐directed physical activity, with varied emphasis on aerobic, strength, endurance, flexibility, and task training. Duration ranged from 8 to 16 weeks. The primary outcome was the modified Unified Huntington's Disease Rating Motor Score. Secondary outcomes included the Symbol Digit Modality Test, Berg Balance Scale, 30‐second Chair stand, Timed Up and Go, Gait Speed, Physical Performance Test, Six‐Minute Walk, International Physical Activity Questionnaire, Hospital Anxiety and Depression Scale, EuroQol Health Utility Index, and Short‐Form 36 Health Related Quality of Life Scale. The primary analysis utilized a two‐stage approach. A one‐stage approach was explored as a sensitivity analysis using a cross‐classified (by study site) linear mixed‐effects model. Results: One hundred twenty‐one participants provided complete data. Risk of bias was moderate; however, primary outcomes were blind assessed. Primary pooled effect estimates adjusted for baseline modified motor score (95% confidence interval) were 0.2 (–2.1 to 2.6) favoring control. There was considerable heterogeneity between the studies. Conclusions: There was no evidence of an exercise effect on the modified motor score in these relatively short‐duration interventions. Longer‐duration trials incorporating supervised components meeting frequency, intensity, time, and type principles are required. Lack of common outcomes limited the analysis and highlight the importance of a core outcome set for evaluating exercise in HD.